Quy trình công nghệ sản xuât bột cá. - Vũ, Hạnh (2011)
Tác giả: Vũ Hạnh, TS; Nguyễn Thị Thu Hằng, KS; Đoàn Văn Tiến, KS; Nguyễn Việt Anh, KS -- Từ khóa: Bột cá; Thiết bị sản xuất bột cá; Thức ăn chăn nuôi